Ion-Isotopic exchange reaction kinetics in characterization of anion exchange resins Dowex 550A LC and Indion-820 - Singare, Pravin U. (Diffusion Fundamentals, 2013)
The present paper involves application of nondestructive radioactive tracer technique in characterization of Dowex 550A LC and Indion-820 anion exchange resins. The characterization study was based on kinetic of exchange reactions between inactive iodide/bromide ions on the resins with radioactive iodide/bromide ions in the solution. During iodide exchange reaction performed at a constant temperature of 40.00C, using 1.000 g of ion exchange resins and labeled iodide ion solution of concentration 0.003 mol/L, for Dowex 550A LC resin the specific reaction rate and initial rate of ion exchange was 0.271 min-1 and 0.141 mmol/min respectively, while the amount of iodide ions exchanged was 0.522 mmol, and log Kd was calculated to be 12.1. The above values calculated for Dowex 550A LC resin was higher than the respective values of 0.108, 0.330, 0.036 and 6.0 as obtained for Indion-820 resins. Similar results were obtained for the two resins during bromide exchange reactions, thereby indicating superior performance of Dowex 550A LC resin over Indion-820 resins.